Mangrove forest composition and structure in Las Perlas Archipelago, Pacific Panama - McGowan, Tom (2010)
Mangrove forest is an important ecosystem that provides many services, but in Panama, as in other countries, they are under threat due to a variety of human activities. Nowadays, large areas of mangroves continue to be lost without been described and lack of management strategies. This study focused on the mangrove structure in the two largest islands, Isla del Rey and Isla San Jose, of Las Perlas Archipelago (LPA), Pacific Panama. Assessment of Landsat satellite imagery revealed loss of mangroves in the LPA of 965ha in the period 1974-1986, and 248ha in the period 1986-2000. The majority of the loss ( > 77%) from the two study islands was due to timber extraction and agricultural development. In May 2006, permanent plots following the CARICOMP protocol were established at two sites on Isla del Rey (R1 and R2) and one site on Isla San Jose (SJ) where standardized metrics such as species, height and diameter at breast height of adult trees and seedlings were recorded. Forest structure differed at the three sites, although R1 and R2 were most similar. At R1, Laguncularia racemosa was the important species and R2 was dominated by Pelliciera rhizophorae. Examination of the forest structure and classified imagery indicated that these sites are spatially dynamic and appear to be rejuvenating. The forest structure would indicate that the sites have been growth-limited previously by human activities and possibly by other factors. SJ was dominated by Rhizophora mangle and appears to have a mature forest with large adult trees and few seedlings. It does not appear to have shown the same extent of spatial regrowth as the other two sites between 1986 and 2000 and is relatively static. The establishment of permanent plots and monitoring will be useful as part of the management plan, as the LPA shows a variety of mangrove structures and could be subject to further coastal development. Rev. Biol. Trop. 58 (3): 857-869. Epub 2010 September 01.